2020
DOI: 10.1007/s00439-020-02190-y
|View full text |Cite
|
Sign up to set email alerts
|

Rare variant association testing in the non-coding genome

Abstract: The development of next-generation sequencing technologies has opened-up some new possibilities to explore the contribution of genetic variants to human diseases and in particular that of rare variants. Statistical methods have been developed to test for association with rare variants that require the definition of testing units and, in these testing units, the selection of qualifying variants to include in the test. In the coding regions of the genome, testing units are usually the different genes and qualify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 112 publications
0
24
0
Order By: Relevance
“…Even though whole genome sequencing data are now more often available on cases and controls, rare variant association tests (RVAT) usually remain restricted to the coding part of the genome. This is explained by the lack of tools to explore rare variant associations outside genes (11). Indeed, RVAT requires the definition of testing units that are easily defined through genes in coding regions and the selection in these regions of the most functionally-relevant variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though whole genome sequencing data are now more often available on cases and controls, rare variant association tests (RVAT) usually remain restricted to the coding part of the genome. This is explained by the lack of tools to explore rare variant associations outside genes (11). Indeed, RVAT requires the definition of testing units that are easily defined through genes in coding regions and the selection in these regions of the most functionally-relevant variants.…”
Section: Discussionmentioning
confidence: 99%
“…This is for example the case in the RNF213 gene where an enrichment in rare variants located in the C-terminal region is found in Moyamoya cases (10). Defining testing units and qualifying variants is also much more challenging in the non-coding genome due to the lack of defined genomic elements and the higher difficulty to predict the functional impact of noncoding variants (11). It is yet a question of interest as several studies have shown the importance of rare non-coding variants in the development of complex diseases (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Determining the impact of rare non-coding variants on TG regulation is a major challenge in the eld of human genetics [23]. Here, we present the utility of our GRN based ENET models for weighting rare variants within kernel-based association tests to improve their power.…”
Section: Accounting For Chromatin Interactions Between Tfbs and Gene mentioning
confidence: 99%
“…However, these methods have limited utility for defining analysis units in the noncoding genome 21 . For example, for gene-centric analysis, STAAR has been used with two noncoding genetic categories of regulatory regions (masks): using promoters and enhancers in GeneHancer 22 overlaid with Cap Analysis of Gene Expression (CAGE) sites 23,24 ; for non-gene-centric analysis, fixed-size sliding windows can be used to scan the genome.…”
Section: Introductionmentioning
confidence: 99%